2019
DOI: 10.1001/jamapediatrics.2019.3203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Immunodeficiency in Children With Invasive Pneumococcal Disease in the Pneumococcal Vaccine Era

Abstract: IMPORTANCE Despite increasing access to vaccination, invasive pneumococcal disease (IPD) is responsible for approximately 826 000 deaths worldwide in children younger than 5 years each year. To allow early identification and prevention, an improved understanding of risk factors for IPD is needed.OBJECTIVES To review the literature on the prevalence of primary immunodeficiency (PID) in children younger than 18 years presenting with IPD without another predisposing condition and to inform guidelines for immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
(290 reference statements)
2
15
0
Order By: Relevance
“…Other alerts to potential PID that are in line with the JMF warning signs that may be more discriminatory include severe bacterial infections (osteomyelitis in 4%, meningitis in 6%, septicemia in 8%, mastoiditis in 8%), which are clearly more frequent than lifetime prevalence in the general population. Recent studies already demonstrated a high incidence of antibody deficiency in patients with pneumococcal meningitis (86)(87)(88), confirming our finding of a high frequency of infectious meningitis in CVID, but we also show a high incidence of bloodstream infections, mastoiditis and to a somewhat lesser extent osteomyelitis in CVID patients. This suggests that the incidence of CVID may also be increased in patients with bloodstream infections, mastoiditis and osteomyelitis without other clear predispositions and suggest screening for CVID could be useful in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Other alerts to potential PID that are in line with the JMF warning signs that may be more discriminatory include severe bacterial infections (osteomyelitis in 4%, meningitis in 6%, septicemia in 8%, mastoiditis in 8%), which are clearly more frequent than lifetime prevalence in the general population. Recent studies already demonstrated a high incidence of antibody deficiency in patients with pneumococcal meningitis (86)(87)(88), confirming our finding of a high frequency of infectious meningitis in CVID, but we also show a high incidence of bloodstream infections, mastoiditis and to a somewhat lesser extent osteomyelitis in CVID patients. This suggests that the incidence of CVID may also be increased in patients with bloodstream infections, mastoiditis and osteomyelitis without other clear predispositions and suggest screening for CVID could be useful in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…5 Primary immunodeficiency has been shown to be more prevalent in pediatric rIPD cases than all pediatric IPD cases (66.7% vs. 1.3-10.5% in a 2019 systematic review). 16 With respect to primary IPD, children over the age of 2 years are more likely to have a primary immunodeficiency. 16 Recurrent IPD, particularly in vaccinated children, has been suggested to be used as an indication for immunodeficiency screening.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed that IPD due to nonvaccine serotypes and/or those with presumed low invasive disease capacity such as 35B and 11A was more prevalent among children with comorbidities [ 8 , 12 ]. In studies of children over 2 years without a predisposing condition, IPD may be a manifestation of an underlying primary immunodeficiency and warrant immune evaluation [ 13 ]. Our patients presented under 2 years of age and had abnormalities detected on immunologic evaluation.…”
Section: Discussionmentioning
confidence: 99%